Time Series Trend in High BMI and High Out-of-Pocket Expenditure Among Women With Disability - Sun Mi Shin PhD (SAGE Publishing, 2023)
Health with disability is directly related not only to an individual's quality of life but also to national medical finance. This study focuses on trends in BMI and out-of-pocket (OOP) expenditure of both types of indirect cost exclusion and inclusion. Participants were women with disability (n = 3200) and women without disability (n = 53 082) among adults aged 19 and older from Korea Health Panel from 2009 to 2016. Women with disability had a higher BMI (23.9) than women without disability (22.7), and this time series trend was significant for 8 years ( P  < .0001). Annual OOP expenditures of both types were higher for women with disability than for women without disability ( P  < .0001): excluding indirect costs, $518.9 versus $649.4; Including indirect costs, $534.5 versus $681.8. The y-intercept of disability itself and slope of one unit of BMI for both types of annual OOP expenditure is significant ( P  < 0001): excluding indirect cost, $29.0 and $4.4; including indirect cost, $35.2 versus $4.6. In women with disability, annual OOP expenditure for both types were higher when they were physically inactive ( P  < .05): excluding indirect cost, $714.1 versus $823.1; including indirect cost, $746.2 versus $880.0. When physical inactivity and overweight and obesity interacted, it increased more than normal weight in dose response manner ( P  < .05): excluding indirect costs, $799.2 < $800.3 < $886.1; Including indirect costs, $860.2 < $845.9 < $927.5. These results suggest that women with disability are in relatively poor health. It is proposed that inequality of BMI for women with disability can be developed as an agenda from health policy.